A study on relationship between work environment and transfer of training at Johor Skills Develoment Centre / Siti Nur Amira Md Najib - Md Najib, Siti Nur Amira (2015)
Transfer of training is important in determining the effectiveness of the training program. One of the criteria to measure the effectiveness of training program is a transfer of training. In particular this study examined the relationship between work environment and transfer of training at Johor Skils Development Centre. A quantitative approach and descriptive research design was use in this study. Three hypotheses were proposed to test the relationship between supervisor support, peers support opportunity to perform and transfer of training among employees at Johor Skills Development Centre. Questionnaires was use to collect the data. The data were analyzed by using Statistical Package for Social Science (SPSS) through Descriptive Statistic, Correlation and Regression. This study use convenience sampling technique to select the sample for this study. Besides that, multiple regression analysis was use to determine the relationship between the variables.